THE IMPACT OF INTERNET AND SOCIAL MEDIA ON THE TRANSFORMATION OF THE STATE MUSEUM OF NEGERI SEMBILAN - Shukri, Shakeerah Mohd; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the relationship between five factors of service quality on visitor’s perception towards the State Museum of Negeri Sembilan services. There were 489 respondents chosen for the analysis. Managerial implication expected the consideration of whether The State Museum of Negeri Sembilan services is a reasonable and meaningful visitor expression in particular service context, the necessity of focusing on surprising level of perception when attempting to predict decision making and potentially separate strategies for including experience and intention. Findings of this study will benefit the State Museum of Negeri Sembilan higher management, State Government, Federal Government, Government agencies, policy maker, students and university by creating insight into visitor perception, intentional behaviour and finally building the decision to visit The State Museum of Negeri Sembilan.